2021
DOI: 10.1155/2021/6249509
|View full text |Cite
|
Sign up to set email alerts
|

Early Perihematomal Edema Expansion: Definition, Significance, and Association with Outcomes after Intracerebral Hemorrhage

Abstract: Objective. To investigate the association between early perihematomal edema (PHE) expansion and functional outcome in patients with intracerebral hemorrhage (ICH). Methods. Patients with ICH who underwent initial computed tomography (CT) scans within 6 hours after the onset of symptoms and follow-up CT scans within 24 ± 12 hours were included. Absolute PHE increase was defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…17,24 Seven studies (n = 4473 patients) assessed the influence of PHO growth on poor functional outcome. 21,23,25,29,36,41,42 Six out of the seven studies measured aPHO increase while one study assessed increase in OED. 23 There was large variation in the interval between symptom onset, baseline PHO measurement and the timing of the assessment of PHO growth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17,24 Seven studies (n = 4473 patients) assessed the influence of PHO growth on poor functional outcome. 21,23,25,29,36,41,42 Six out of the seven studies measured aPHO increase while one study assessed increase in OED. 23 There was large variation in the interval between symptom onset, baseline PHO measurement and the timing of the assessment of PHO growth.…”
Section: Resultsmentioning
confidence: 99%
“…37 Combining these two studies 28,37 with the studies included the primary analysis, 22,24,30,38 we found a pooled OR of 1.02 (95% CI 1.00-1.04, p = 0.1, I 2 = 76%) for the association between PHO and mRS 3 and 6 at any time of follow-up. Seven studies (n = 2793 patients) 25,27,29,31,36,39,42 reported on the influence of PHO and mRS score 4-6 at 3 months. Three of these studies (n = 1398) 25,36,42 assessed PHO growth as their primary analysis, the other four (n = 1395) 27,29,31,39 measured aPHO.…”
Section: Resultsmentioning
confidence: 99%
“…The pre-clinical research on magnetic resonance spectroscopy revealed that the recovery of N-acetylaspartate, choline, and creatine was faster in the PHE area than in the non-PHE area ( 31 ), suggesting that the PHE may provide a protective buffer against irreversible impairment. Nevertheless, real-world research showed that patients with absolute ( 15 , 32 , 33 ) and relative PHE expansion ( 5 , 16 ) have a higher risk of developing poor neurological outcomes. Compared to the well-established research for hematoma expansion, we believe the PHE expansion is worthy of further investigation based on its good sensitivity for prognosis prediction, and a more comprehensive prediction model for PHE expansion is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The growth of PHE measured by PHE expansion and EED was also used to evaluate the severity of brain edema after ICH in patients. Two clinical studies have found that an increase in absolute PHE volume from baseline to day 3 was correlated with a poor outcome 3 months after ICH [ 116 , 179 ]. A study with 115 patients also found that the PHE expansion rate from baseline to 72 hours was associated with poor functional outcomes after deep ICH [ 180 ].…”
Section: Phe and Functional Outcomesmentioning
confidence: 99%